Factors Relating To Community Preparedness In Facing Flood Disaster In Makassar - Baso Witman Adiaksa (USN Scientific Journal, 2020)
Flood preparedness is not only carried out by the government, the community also needs tocarry out disaster preparedness in order to reduce losses due to disasters. Preparednessefforts for each individual or group are not the same depending on the level of disasterpreparedness which is influenced by socio-demographic factors, social networks, andexperiences. natural or non-natural disaster. The purpose of this study, namely to determinethe factors related to the preparedness of the Tamangapa community in facing flooddisasters in Tamangapa Village, Manggala District, Makassar City. This study used aresearch design with a cross sectional design, namely to determine the correlativerelationship between factors related to community preparedness in facing disasters. Thepopulation in the study These are all family heads registered in RW 06 who livepermanently as residents of Tamangapa Village, Manggala District, as many as 400 with 80random sampling techniques. The analysis was carried out by using the Pearson Chi Squaretest. The data were analyzed using the SPSS 1 7 program. The results showed that therewas a relationship between knowledge, attitudes and experience with communitypreparedness in facing flood disasters in RW 06, Tamangapa Village, Manggala District,Makassar City